1998
DOI: 10.1111/j.1469-7793.1998.857bv.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor modulation of human cortical swallowing pathways

Abstract: Transcranial magnetic stimulation over motor areas of cerebral cortex in man can activate short latency bilateral cortical projections to the pharynx and oesophagus. In the present paper we investigate the interaction between pathways from each hemisphere and explore how activity in these pathways is modulated by afferent feedback from the face, pharynx and oesophagus. Comparison of unilateral and bilateral stimulation (using interstimulus intervals (ISIs) of 1, 5 or 10 ms between shocks) showed spatial summat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 25 publications
5
55
1
1
Order By: Relevance
“…However, pharyngeal stimulation, being more direct, might only activate the corticopharyngeal pathway without altering excitability in other cortical swallowing networks and hence not affect the "reflex" response. Against this notion is the fact that following volitional swallowing (and with anesthesia) there were latency shifts in both pathways, which are more typically seen when motoneurons in the bulbar nuclei and/or muscle are depolarized (7). At present, our data cannot fully resolve the issue of the nature of the reflex pathway, and consequently this remains open to further study.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…However, pharyngeal stimulation, being more direct, might only activate the corticopharyngeal pathway without altering excitability in other cortical swallowing networks and hence not affect the "reflex" response. Against this notion is the fact that following volitional swallowing (and with anesthesia) there were latency shifts in both pathways, which are more typically seen when motoneurons in the bulbar nuclei and/or muscle are depolarized (7). At present, our data cannot fully resolve the issue of the nature of the reflex pathway, and consequently this remains open to further study.…”
Section: Discussionmentioning
confidence: 40%
“…These afferent fibers are not only capable of influencing brain stem motoneuron and interneuron excitability but also that of higher circuitry in the cerebral cortex (12,18,19). Indeed, previous TMS studies (6,7) have shown that excitation of (afferent) pathways in cranial nerves V and X, for example from the face or neck, produces a "reflex" response in the human pharynx and esophagus that is likely to be generated via neurons within the brain stem and possibly through the central pattern generator itself. Stimulation of these craniobulbar responses, when combined with cortical input, produce short-term (100-200 ms) facilitation of the cortically evoked pharyngeal and esophageal re-sponses, suggesting that both pathways involve similar populations of bulbar neurons.…”
mentioning
confidence: 99%
“…9 Stimulation of whiskers in rats enhances c-fos expression, 10 which has been postulated to upregulate the expression of neurotrophins that may be involved with dendritic and axonal sprouting. SS enhances excitability of the stimulated body part representation in the motor cortex in healthy subjects 6,11 and results in improvements in motor performance in stroke patients. 11, 12 Our results demonstrate that this intervention may enhance the beneficial effects of a single motor training session on UDP in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…SS enhances excitability of the stimulated body part representation in the motor cortex in healthy subjects 6,11 and results in improvements in motor performance in stroke patients. 11, 12 Our results demonstrate that this intervention may enhance the beneficial effects of a single motor training session on UDP in stroke patients. Combination of SS with training protocols could conceivably be applied in the future to improve the effects of customary rehabilitative interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The application of electrical stimulation, both externally to the submental region and internally to the pharynx has been explored [2][3][4].…”
Section: Introductionmentioning
confidence: 99%